Masorah rearranged: eight masoretic lists in MS London Oriental 2091, fol. 335v - Liss, Hanna (Corpus Masoreticum working papers, 2023)
This paper deals with eight masoretic lists that are found on fol. 335v in MS London BL or. 2091. All lists on this folio are found in situ. The folio contains three figuratae, of which the first and the third encompass two lists each, whereas the middle figurata displays four. Lists 1 and 3 to 8 are complete, and only list 2 is incomplete. The paper explains the lists at hand and relates them to both the Okhla we-Okhla recensions (Halle/Paris) and to some Tiberian manuscripts, e.g. Firkovich, Evr. I B 19a, Codex Babylonicus Petropolitanus (St. Petersburg, Russian National Library, Firkovich, Evr. I B 3), MS JTS Lutzki 232 (E. N. Adler Ms. 346). In addition to the philological comparisons, I will address some initial questions regarding aesthetic aspects and the methods used by the masran to put his material to parchment.